Morphine Consumption and/or Numerical Scale in Pain Studies: Silverman Integrating Approach (SIA SCORE) - Laouamri, Okba (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Ligamentoplasty pain management is dynamic performance, demanding constant vigilance and adaptation. The aim of this prospective study was to compare the analgesic efficacy of three techniques for knee ligamentoplasty using an integration score, the SIA score. Methods: The study included 165 patients undergoing primary reconstruction of the anterior cruciate ligament of the knee. The first group, systemic analgesia (SA), received balanced systemic analgesia postoperatively for a minimum of five days, based on Paracetamol, Diclofenac, and a morphine PCA. In addition to the systemic analgesia already described, the second group, femoral analgesia (FA), will benefit from a femoral peri-nervous catheter in the crural position. The third intra-articular analgesia (IAA) group received, in addition to the same systemic analgesia, an infusion through an epidural catheter of 20 ml of 0.125% bupivacaine, followed by maintenance with 8 ml/h of the same local anesthetic via an electric syringe pump for 36 h. Cumulative morphine consumption was assessed, as well as pain at rest, using a numerical scale (EN) from 1 to 10 and an integration of these two parameters. Results: Morphine consumption was lower in the AF group. The lowest mean rank was in the AF group, followed by the AIA group, and the difference was statistically significant with an H = 6.89 and a p= 0.032. The difference was significant between the AS group and the AF group (p = 0.09); the other inter-group differences were not significant. 23.2% of patients had an AIS score between [-100, -200], and were in little pain and consumed little morphine (effective treatment); 14.2% of patients had an AIS score between [100, 200] and were in great pain and consumed a lot of morphine (morphine-resistant or very sensitive to pain). Conclusion: Analgesia in the femoral peri-nerve group was more effective, with a reduction in mean EN compared with the other two groups.